A utilização do livro didático em aulas de química - Kato, Cláudia Mikie (2014)
The textbook is one of the main tools of the use of teachers and students from basic education and has an influence on the teaching learning process. Despite its importance, still few studies about its use in class. Therefore, this research aimed to investigate the use of this feature by high school first grade teachers and students of state public schools from a town located in Paraná State. Thus, to understand such processes, it was performed a qualitative research by means of a participative observation of five high school first grade classes, besides interviewing five teachers and twenty students from these classes. As main results, we find out that the book is a resource for teachers for planning and organizing their pedagogical work. Furthermore, the main ways to use the textbook by teachers and students are linked to attending to the contents explanation, to doing exercises, to copying certain content and to observing figures and graphs. We identified gaps concerning the traditional use of an innovative book by P2 (Teacher 2). These gaps occurred because the choice for a book with such characteristics was not based on the approach proposed by the textbooks authors, but by giving priority to the content of the PAS (Serial Evaluation Process) exam. Concerning the education of the interviwed teachers, despite the specific skills and career levels of each of them, we noticed a homogenization of their classes, not to mention the lack of alternative approaches by them. Hence, the use of the book could be guided by means of an initial and continuous education, in order to provide a more appropriate exploitation of their potential and then to contribute effectively to the practice of teaching.